2008
DOI: 10.1007/s00383-008-2148-2
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal outcome of antenatally diagnosed intra-abdominal cysts

Abstract: Objectives: To assess the postnatal outcomes following prenatal ultrasound diagnosis of fetal abdominal cyst at our institution. Methods: We identified all fetal abdominal cysts diagnosed between 2005 and 2016 using our ultrasound database. The fetuses were monitored during the pregnancy to assess their antenatal course. Follow-up was continued during childhood to determine the postnatal diagnosis and outcome. Results: We found 80 cases of abdominal cysts. The antenatal diagnosis was thought to be of ovarian o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 11 publications
4
26
3
Order By: Relevance
“…Accordingly, Özyüncü et al reported overall spontaneous mortality rate to be 11/64 (17%). Intrauterine deaths in our series were 2/17 (11.8%), while this was found to be 3.6% and 4.2% in previous reports, respectively (1,21). We think this difference arises from the inclusion criteria of the study groups.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Accordingly, Özyüncü et al reported overall spontaneous mortality rate to be 11/64 (17%). Intrauterine deaths in our series were 2/17 (11.8%), while this was found to be 3.6% and 4.2% in previous reports, respectively (1,21). We think this difference arises from the inclusion criteria of the study groups.…”
Section: Discussioncontrasting
confidence: 76%
“…Fetal abdominal cysts (FAC) can originate from renal, intestinal, mesenteric, ovarian, hepatic, and biliary systems (1). In the differential diagnosis, it is difficult to define the precise etiology of FAC prenatally.…”
Section: Introductionmentioning
confidence: 99%
“…The mean gestational age of liveborn cases was 37.4 weeks ( 8 2.27) and the mean birth weight was 2,907.2 g ( 8 554.71). Surgery was (1) ileal atresia (1) intestinal obstruction (4) ileal atresia (2) intestinal atresia (1) urogenital sinus abnormality (1) jejunal atresia (2) jejunal atresia (2) Mesenteric (2) mesenteric (2) mesenteric (1) normal (1) Ovarian (14) ovarian cyst (14) ovarian cyst (8) mesenteric cyst (2) normal (4) Genitourinary (21) double collecting system (1) double collecting system (1) megacystis-PUV (13) megacystis-PUV (8) renal cystic dysplasia (1) urogenital sinus abnormality (2) normal (2) pelviectasis (1) pelviectasis (1) renal cyst (5) megaureter (1) ( table 1 ), 36 had uniloculated, 13 biloculated, 2 solid, and 20 multiloculated complex appearance. Among the uniloculated simple cystic lesions, the most common localization was in the right (17) and upper (11) quadrants.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the advancing imaging technologies, the detection rates of ultrasonography in the identification of the origin of fetal abdominal cysts are still far below expectations. Therefore, the diagnosis is reported to be imprecise, and prediction of neonatal intervention is poor [4,9] , both of which complicate the counseling and management of the case [3] . The positive predictive value of ultrasonography in the identification of the cysts' origin on a system basis in our series approached 75%, meaning that one-fourth of the cysts diagnosed as intra-abdominal cysts antenatally actually involved other systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation